Reflection on action: peer micro-teaching process of prospective EFL teachers and class teachers focusing on mother tongue teaching - Ćirković Miladinović, Ivana; Dimitrijevic, Maja; Ilic, Branko (Technium Social Sciences Journal, 2021)
Teaching experience plays a productive role in teacher professional development, so it is necessary to examine such experience systematically, either as reflection on action or reflection in action. In a sense, reflection has the power to help the teacher connect experience and theoretical knowledge and to use each area of expertise more efficiently (Knezevic and Scholl 1996). Therefore, reflection is an important ‘tool’ to articulate how we know what we do when we teach (ibid.). For this reason, micro-teaching is an opportunity to link theory and practice, critically evaluate one’s teaching skills and to discuss alternative approaches and solutions for the specific teaching context with peer colleagues. This paper will focus, firstly, on the micro-teaching process by explaining the background of this procedure and then by giving the detailed description of the two micro-teaching sessions conducted in January and February 2020 at the Faculty of Education in Jagodina, University of Kragujevac, Serbia. Secondly, it will consider giving feedback to others, in person and online, using video records, self-evaluation and reflection in peer-teaching process. Finally, the paper will evaluate two peer micro-teaching sessions with a focus on student-student, interaction in university teaching context and advantages and disadvantages in teaching English as a foreign language on one side, and Serbian as the mother tongue on the other.